Keeping “critical” critical: A conversation from Culture on the Edge - Martin, Craig (Critical research on religion, 2014)
In early March 2014, some of the members of Culture on the Edge—a scholarly research collaboration of seven scholars of religion, interested in more theoretically sophisticated studies of identity, and all of whom are at different career stages and at a variety of North American institutions—had a conversation online on the use of the terms “critique” and “critical,” terms widely used in the field today but employed in such a variety of ways that the members of the group thought it worthwhile to focus some attention on them. What follows is the transcript of their conversation.